Violence against children and issues of identifying violence in preschool institutions - Nikoladze, Marekhi; Mamrikishvili, Nino (International Scientific Conference “EDUCATION, RESEARCH, PRACTICE” Proceedings, 2024)
The „Convention on the Rights of the Child“, which Georgia joined in 1994, instructs the participating states to protect children from all forms of violence, although studies and information disseminated through mass media show that children in our country are still not protected from violence, or are inadequately protected. The issues of protecting the rights of pre-school children representing ethnic minorities are particularly serious and still unexplored. Therefore, in addition to preventive measures, the issues of responding to the facts of violence are still relevant. Procedures (government decree) for child protection apeal (referral) include response mechanisms in case of child abuse, however, our research has shown that the level of awareness of the staff of the entities (kindergartens) involved in the referral process, about their rights and duties in this process, is low. Most of the interviewees are not familiar with all forms of violence and it is difficult for them to identify the fact of violence. Specialists in daily contact with children play a key role in this process. Therefore, we think that it is necessary for the state to conduct a mass campaign regarding the reporting of cases of violence, to train educators and equip them with the necessary resources. It is also important that professional and undergraduate programs related to pre-school education include issues related to violence against children, responses to it, and prevention by promoting the growth of parental awareness.